Agribusiness Control in Philippine Contract Farming: From Formality to Intervention - Vellema, Sietze (The International Journal of Sociology of Agriculture and Food, 2021)
This article discusses the capacity of a division of the Dole company to direct the farming practices, labor use, and production costs of Philippine contract growers. The production of asparagus for the Japanese market was contracted out by a division of Dole Food in the Philippines, and was part of the company’s expansion and diversification program. By utilizing an ethnographic approach, this study contributes to a precise understanding of the interaction between agribusiness and growers. The article describes how control shifted away from hands-off management to an interventionist hands-on management of the contracted farms. In the beginning of the asparagus scheme the company mainly focused on controlling marketing and credit flows. After unforeseen increases in labor costs, management decided to intervene in the labor management practices of growers and to introduce new technologies in an effort to sustain the profitability of the production scheme. The case-study highlights the social and technical shaping of control and reveals the negotiated nature of farming practices.